A Case of Treatment Resistant Depression and Alcohol Abuse in a Person with Mental Retardation: Response to Aripiprazole and Fluvoxamine Therapy upon Consideration of a Bipolar Diathesis after Repetitive Failure to Respond to Multiple Antidepressant Trials - Michele Fornaro; Giovanni Ciampa; Nicola Mosti; Alessandra Del Carlo; Giuseppe Ceraudo; Salvatore Colicchio (Case Reports in Medicine)
Mental Retardation (MR) is a developmental disability characterized by impairments in adaptive daily life skills and difficulties in social and interpersonal functioning. Since multiple causes may contribute to MR, associated clinical pictures may vary accordingly. Nevertheless, when psychiatric disorders as Treatment Resistant Depression (TRD) and/or alcohol abuse co-exist, their proper detection and management is often troublesome, essentially due to a limited vocabulary MR people could use to describe their symptoms, feelings and concerns, and the lack of reliable screening tools. Furthermore, MR people are among the most medicated subjects, with (over) prescription of antidepressants and/or typical antipsychotics being the rule rather than exception. Thus, treatment resistance or even worsening of depression, constitute frequent occurrences. This report describes the case of a person with MR who failed to respond to repetitive trials of antidepressant monotherapies, finally recovering using aripiprazole to fluvoxamine augmentation upon consideration of a putative bipolar diathesis for “agitated” TRD. Although further controlled investigations are needed to assess a putative bipolar diathesis in some cases of MR associated to TRD, prudence is advised in the long-term prescription of antidepressant monotherapies in such conditions.